A classroom project for the formation of child readers and writers - Carreño Vasquez, Ingrid; Ardila León, Marisol (Rastros Rostros, 2002)
The construction of theories that contribute to the formation of readers and producers of texts is the concern of experts and scholars of the subject. These theories leave behind the traditional methods because they required a lot of effort and were not very rewarding. Today, most of them accept that the learner's participation, ideas and feelings are very important in educational processes.